Magnitude Clustering During Stick‐Slip Dynamics on Laboratory Faults - Omid Khajehdehi; Thomas H. W. Goebel; Georg Dresen; Jörn Davidsen (Geophysical Research Letters, 2024)
Abstract We present an analysis of magnitude clustering of microfractures inferred from acoustic emissions (AEs) during stick‐slip (SS) dynamics of faulted Westerly granite samples in frictional sliding experiments, with and without fluids, under triaxial loading with constant displacement rate. We investigate magnitude clustering in time across periods during, preceding and after macroscopic slip events on laboratory faults. Our findings reveal that magnitude clustering exists such that subsequent AEs tend to have more similar magnitudes than expected. Yet, this clustering only exists during macroscopic slip events and is strongest during major slip events in fluid‐saturated and dry samples. We demonstrate that robust magnitude clustering arises from variations in frequency‐magnitude distributions of AE events during macroscopic slip events. These temporal variations indicate a prevalence of larger AE events right after (0.3–3 s) the SS onset. Hence, magnitude clustering is a consequence of non‐stationarities.